«Szopki i hałaburdy». Osyp Nazaruk o Polsce i o Polakach - Gaczkowski, Marcin (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Osyp Nazaruk 1883–1940 was a Ukrainian lawyer, politic, publicist and novelist descended from Galicia. His literary production is devoted mainly to Ukrainian-Polish neigbourhood. In historical literature Nazaruk is known as a proponent of Ukrainian agreement during the inter-war period as well as a supporter of taking the “real» loyal to Warsaw political course by Ukrainian politics in the second Polish Republic. The article analyzes Nazaruk’s journalistic production from almost forty years. Separate subsections are devoted to the Ukrainian-Polish relations – in Nazaruk’s analysis – at the beginning of the 20th century, during World War I and the Ukrainian revolution, the second Polish Republic as well as during World War II. In his writing a generally negative stereotype of Poles and Poland dominates, however, his approach varies depending on many factors.
Keywords: Nazaruk, Osyp; relacje ukraińsko-polskie; stereotypy narodowościowe; mity historyczne; Galicja Wschodnia